Vacuum distillation and ab initio molecular dynamic simulation of Al–Li alloys. (April 2023) - Shi, Lei; Jia, Liru; Ning, Ping; Sun, Xin; Wang, Chi; Ma, Yixing; Wang, Fei; Qu, Tao; Li, Kai
Abstract: Al–Li alloys, which offer excellent properties, are widely used in aviation, high-speed railway and other fields. The amount of scrap produced will increase as the alloy content increases. Therefore, it is important to study the recovery of Al and Li from Al–Li alloys. In this study, the theories of saturated vapor pressure and vapor–liquid equilibrium composition are adopted to determine the possibility of separating Al from Li, and the results show that Al–Li alloys decomposition by vacuum distillation is feasible. In addition, it is determined that Li and Al can be recycled in the gas and liquid phases, respectively. The separation of Al-7.87 wt% Li alloy by vacuum distillation was studied. The results indicated that, at a pressure of 10 Pa, a distillation temperature of 1223 K, and a soaking time of 60 min, the volatilization and recovery rates of Li were 99.77 wt% and 80.65 wt%, respectively. The lithium content in the condensate was 99.72 wt%, while that of Al was 99.98 wt%. Using AIMD to analyze the Al-7.87 wt% Li alloy melt over a range of 700–1473 K, the simulation results were found to be consistent with the experimental results and thus could be applied to the planning of vacuum distillation. Highlights: Saturated vapor pressure, the vapor–liquid phase equilibrium diagram and ab initio molecular dynamics provide guidance for the research on the recovery of Al-7.87%Li alloy by vacuum distillation. Under vacuum conditions, the Al-7.87% Li alloy can be separated effectively, and the purity of 99.72%Li and 99.98%Al can be obtained in the gas and liquid phases, respectively. AIMD can be used to forecast the best experimental temperature for the vacuum distillation of alloys. It provides an efficient and convenient means of guiding vacuum metallurgy.